Are Ayurvedic medications store house of heavy metals?. Issue 1 (15th January 2022) - Bhalla, A; Pannu, A K
Abstract: Ayurvedic formulations are widely used and perceived as safer medicine and subjected to be self-prescribed. However, recent reports have demonstrated adulterating these drugs with toxic quantities of heavy metals. To study the magnitude of the problem in Indian-manufactured Ayurvedic medications, we randomly collected common over-the-counter Ayurvedic preparations from the licensed Ayurvedic shops in the local markets of Chandigarh in 2017. The samples were analyzed to identify and quantify eight metal ions, including mercury, arsenic, lead, cadmium, zinc, iron, copper, and chromium, using inductively coupled plasma mass spectrometry in Postgraduate Institute of Medical Education and Research, Chandigarh. The permissible limit set by the Food and Agriculture Organization/World Health Organization (FAO/WHO) for herbal medicines was followed to define the high metal concentrations. Out of 43 Ayurvedic preparations, 42 were analyzed. Heavy metals were detected in all formulations. The median (range) concentrations (in μg/g or mg/kg) of the metals were quantified as follows- mercury, 13.52 (0.00–61 095.99); arsenic, 0.00 (0.00–1038.83); lead, 1.40 (0.00–57.09); zinc, 84.2200 (26.48–22 519.03); iron, 1356.21 (128.24–136 835.25); copper, 17.1450 (0.00–12 756.86) and chromium, 20.9050 (0.00–2717.58). The metal contents above the FAO/WHO-mandated limit for zinc, mercury, arsenic, and lead were detected in 35, 29, 6, and 2 formulations, respectively. All medications contained detectable quantities of zinc and iron. Copper was detected in all except one. Cadmium was not found in any sample. Ayurvedic medications have a high prevalence of heavy metals. An evaluation of the sources of contamination and the necessary drug safety regulations are required.